On the Power of the Empowering Transformation of Femininity in Pictures-Dreams by Izabela Alicja Cern - Juchacz, Piotr W. (Sensus Historiae, 2023)
This text is a philosophical-cultural interpretation of Izabela Alicja Cern’s photographs—artistic portraits of women—presented during the vernissage ‘Follow the White Rabbit’, which took place at the Gallery of Miscellaneous Arts in Poznań in the spring of 2022. The key to the interpretation are the characters from Lewis Carroll’s Alice in Wonderland, read as women who are, on the one hand, selfempowering and, on the other, powerfully transforming the world around them.